Analysis of Crime Actions of Human Rights Violations Performed by Mynmar Against its Rohing Ethnic View from an International Criminal Law Perspective - Cantika Ramadhani Bintang; Nadia Fraselia; Rafin Subhan S, Herli Antoni; Asmak Ul Hosnah (Global Scientific Publishing, 2023)
Human Rights Violation (Human Rights) is a felony that causes or wounds many victims, and then it is committed intentionally and by accident in order to injure or deprive a person of his human rights. In the casa of Myanmar's attack on her ethnicity rohing.In this act,many of the crimes of human rights absues such as the difference in status,rape,murder and unrecognized civil rights by the government of Myanmar,even the police and Myanmar soldiers have also contributed to provoking some of the Myanmar ethnic attacks agnaist her prit.Then in 2017 Mynmar made an effort to purge his rihing ethnia in the event Mnynmar also committed the brutal act of assaulting his rihing-ethnic in raukhure province. The rohinge has undergone various forms of human rights violations sice 1938.So the problem that can be raised from this journal is that the mynmar governors' actions to its Rohingne are a form of human rights violation because many of its rohinge do not feel that there is freedom between caste and religion and the act of economic crisis that causes the rohinge to become difficult. Writing this journal is using the normative method that is using the method of literature, The basis of Theories and options of experts. An attempt to make the case obsolete is the first way to stop the existence of violence wherever it is psychical pr other is detrimental to human rights
Keywords: Violation; Human Rights; Confection